Evaluation of optimal waste management in the plating industry based on the Delphi Method and Fuzzy Analytic Hierarchy Process (Case Study: Paitakht Industrial District of Tehran) - Mina Moeeni; Ghasemali Omrani; Nematollah Khorasani; Reza Arjmandi (Environmental Energy and Economic Research, 2020)
The plating industry is one of the main toxic chemicals consumers, which uses various chemicals, including solvents, acids, bases, cleansers, sophisticated organic ingredients, and metal salts of cadmium, nickel and chromium. Due to the growing production of industrial waste in spite of actions related to these wastes’ management, no comprehensive pattern was introduced at different levels. This research uses equipment and standards, including techniques such as Multi-Criteria Decision Supporting System and Fuzzy Analytic Hierarchy Process, to rank and prioritize the participation contribution of the factors that are effective in optimizing the management of waste from the plating industry in a case study, implementing the model on Paitakht Industrial District of Tehran. In order to evaluate waste management situation in the metal plating industry, an integrated empirical model with principles and concepts of Balanced Scorecard Method was used, and factors were identified using the Delphi method. Variation range related to total score based parameters were calculated by the scalographic method, and the significance of the linear relationship between them was analyzed using linear regression in order to determine industrial waste management at three levels, including weak, moderate, and appropriate, presentingthe final pattern. The results showed that waste management in the plating industry, as a sample of special waste and residue, was at a low level. Considering to outputs from the represented pattern, to improve industrial waste management in first priority considered, item interpretation and proceeding to medium-term strategic planning were provided to eliminate the limitations and mentioned issues.